Environmental Ethics in Islamic Religious Education: Promoting Sustainable Behaviors among Students in Nigeria - Chika Jacinta Chinemerem (https://ejournal.insuriponorogo.ac.id/, 2026)
Environmental degradation, climate change, deforestation, pollution, and unsustainable resource consumption have become major global concerns requiring immediate educational responses. In Nigeria, environmental challenges such as desertification, flooding, waste mismanagement, deforestation, and pollution increasingly threaten ecological sustainability and public well-being. Islamic Religious Education (IRE) has the potential to contribute significantly to environmental awareness and sustainable behaviors by integrating environmental ethics grounded in Islamic teachings. This study examines the role of environmental ethics in Islamic Religious Education in promoting sustainable behaviors among students in Nigeria. Using a qualitative literature review approach, the study analyzes scholarly publications, educational reports, and Islamic environmental perspectives related to sustainability education. The findings indicate that Islamic environmental ethics positively influence students’ awareness, attitudes, and behaviors toward environmental conservation through teachings emphasizing stewardship (khalifah), responsibility (amanah), moderation (wasatiyyah), and prohibition of environmental destruction (fasad). Islamic Religious Education provides opportunities to encourage environmentally responsible behaviors such as waste reduction, water conservation, sustainable consumption, and community environmental participation. However, challenges including limited environmental integration in curricula, insufficient teacher preparedness, inadequate educational resources, and weak environmental awareness among communities remain obstacles to implementation. The study concludes that strengthening environmental ethics within Islamic Religious Education can contribute significantly to fostering sustainable student behaviors in Nigeria. Effective implementation requires curriculum reform, teacher professional development, community involvement, and integration of religious teachings with contemporary environmental challenges.